1969
DOI: 10.3758/bf03210103
|View full text |Cite
|
Sign up to set email alerts
|

Eye-movement parameters and pattern discrimination

Abstract: Fig. 1. Schematic of stimulus. Stimuli always contained a center standard pattern surrounded by eight other patterns of asterisks, some of which matched the standard (called targets) and some of which differed from the standard (called nontargets).Second, the effects on eye-movement parameters of the size of the matrix from which patterns were generated was assessed. Patterns were generated from 4 by 4, 6 by 6, 8 by 8, and 10 by 10 matrices. The larger the matrix size, the larger the average number of elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1

Year Published

1973
1973
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 33 publications
5
20
1
Order By: Relevance
“…2, 3, and 4) confirm the previous fmdings that Ss do fixate for different durations at different locations (Mackworth & Morandi, 1967;Gould & Dill, 1969). They also extend the previous fmdings by indicating that Ss differentially fixate within the silhouettes of the type of figures that have often been used in form-perception studies.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…2, 3, and 4) confirm the previous fmdings that Ss do fixate for different durations at different locations (Mackworth & Morandi, 1967;Gould & Dill, 1969). They also extend the previous fmdings by indicating that Ss differentially fixate within the silhouettes of the type of figures that have often been used in form-perception studies.…”
Section: Discussionsupporting
confidence: 76%
“…It has been shown that, when confronted with patterns, especially large ones, Ss tend to fixate successively on more than one element, in a systematic fashion related to the individual stimulus and to the elements within it that contain the most information (Mackworth & Morandi, 1967;Gould & Dill, 1969). The studies cited, unlike the one to be described.…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…The ability to Ss to extract a limited amount of infonnation from stimuli which are not being fixated (i.e., stimuli which project outside of the foveal area of the retina) has been reported by Sanders (1970), Gould and Dill (1969), and Williams (1967). In the study by Gould and Dill, Ss determined how many of the eight test patterns matched a standard pattern while frequency and duration of eye fixations were recorded.…”
Section: Experiments IIImentioning
confidence: 99%
“…Studies of eye movements made during a task involving visual search and pattern discrimination (Gould & DilL 1969) indicate that stimuli can be discriminated grossly in the periphery of the eye and only require foveal foxation for finer discriminations. A related study by Williams (I967) found that Ss selected objects in the extrafoveal field much better on the basis of color than on the basis of size or shape.…”
mentioning
confidence: 99%